Synchronization for different opinions in Malaysia Multiracial Society: a mathematical exploration study - Kamal Koh, Hasna Heng (2017)
Malaysia is known for the multiracial and multicultural society who lives together harmoniously despite of the diversities. The tolerance of the people towards each others’ culture and religions has always been the subject of interest for social science researchers. The harmony is due to the phenomena of synchronization of the notions among the community. Synchronization has been widely studied since it is a natural phenomena happening around us everyday, such as the synchronization of fireflies flashes at night. In relate of these, we anticipate in the study of the synchronization of the opinions in a diverse society with mathematical modelling. In this thesis, we analyse three different methods of synchronization by 3 different models: Kuramoto model, Opinion Changing Rate model and a linear model associate with the famous Friedkin and Johnsen Model. We first develop a modified version of existing mathematical models and then conduct the numerical experiment on the models to utilize them in the desired framework.